Exploring the use of an iPhone App: A Novel Approach to Dietary Assessment - Melissa Keeney; Ming-Chin Yeh; Rissa Landman; May May Leung; Ann Gaba; Khursheed Navder (International Journal of Nutrition, 2016)
Recent advancements in smartphone technology have provided new methods of dietary assessment. An iTunes application (app) called Meal Snap lets users take pictures of the meal they eat, and then estimates the calories of the food items eaten. We conducted a pilot study to explore the user-friendliness and calorie estimation functions of the Meal Snap app. Two female nutrition graduate students pilot-tested the Meal Snap app. Using the app, each student took pictures of foods and drinks consumed daily for two weeks. The data were analyzed using the Nutritionist ProTM software, version 4.4.0. The mean daily caloric intake obtained from the Meal Snap was then compared with that of Nutritionist ProTM. Paired samples t-tests and correlations were carried out using SPSS, version 19.Results indicated there was no significant difference in mean daily caloric consumption between Meal Snap and Nutritionist ProTM (p= 0.706). Additionally, there was a significant correlation between Meal Snap and Nutritionist ProTM calorie counts (Spearman r= 0.625, p< 0.001). It took about 35 minutes per week (or 5 minutes/day) to snap pictures and edit descriptions, whereas entering data for calorie analysis with Nutritionist ProTM took about 85-90 minutes per week (about 13 minutes/day).Findings suggest that Meal Snap may be a user-friendly tool to estimate dietary intake. Future research should include a larger sample and people of diverse ethnic backgrounds, dietary habits and age groups.
Keywords: dietary assessment